Report of the Technical Consultation between Malawi, Mozambique and Tanzania on the Development and Management of the Fisheries of Lake Malawi/Niassa/Nyasa : (Food and Agirculture Organization of the United Nations, 2005)
The Meeting reviewed the decision of the twenty-sixth session of the Committee on Fisheries of relevance to Regional Fishery Bodies. The Meeting discussed the role of RFBs, external factors affecting fisheries management, harmonization of catch documentation, relations between RFBs and the United Nations Environment Programme and the status of the Fisheries Resources Monitoring System and other related matters. The Meeting reached a number of conclusions regarding matters meriting the attention of RFBs, governments and FAO.